Species composition and temporal distribution of mosquito populations in Ibadan, Southwest Nigeria (2014)
Nigeria has a high burden of vector borne diseases such as malaria and lymphatic filariasis (LF). This study aimed to determine the species composition of mosquitoes in Ibadan, Southwest Nigeria as well as determine their role in malaria and LF transmission. Adult mosquitoes were collected by Pyrethrum Spray Catch (PSC) and identified and graded according to their abdominal conditions. The mosquitoes were dissected to determine the parity status and to check for microfilariae of Wuchereria bancrofti. The presence of circumsporozoite protein of Plasmodium falciparum was examined using ELISA. A total of 1600 mosquitoes were collected of which 31 (1.9%) were Anopheles gambiae s. l. while 1756 (98%) were Culex sp. None of the mosquitoes examined was positive for Plasmodium falciparum and Wuchereria bancrofti. The lack of adequate sanitary conditions in the area could be responsible for the large number of mosquitoes collected. Health education could help in sensitizing the inhabitants.